Domesticating Vigna Stipulacea: A Potential Legume Crop With Broad Resistance to Biotic Stresses - Takahashi, Yu; Sakai, Hiroaki; Yoshitsu, Yuki; Muto, Chiaki; Anai, Toyoaki; Pandiyan, Muthaiyan; Senthil, Natesan; Tomooka, Norihiko; Naito, Ken (Frontiers in Plant Science, 2019)
Though crossing wild relatives to modern cultivars is a usual means to introduce alleles of stress tolerance, an alternative is de novo domesticating wild species that are already tolerant to various kinds of stresses. As a test case, we chose Vigna stipulacea Kuntze, which has fast growth, short vegetative stage, and broad resistance to pests and diseases. We developed an EMS-mutagenized population and obtained three mutants with reduced seed dormancy and one with reduced pod shattering. We crossed one of the mutants of less seed dormancy to the wild type and confirmed that the phenotype was inherited in a Mendelian manner. De novo assembly of V. stipulacea genome, and the following resequencing of the F2 progenies successfully identified a SNP associated with seed dormancy. By crossing and pyramiding the mutant phenotypes, we will be able to turn V. stipulacea into a crop which is yet primitive but can be cultivated without pesticides.